Transcatether Aortic Valve Implantation to Treat Degenerated Surgical Bioprosthesis: Focus on the Specific Procedural Challenges - Aurigemma, Cristina; Burzotta, Francesco; Vergallo, Rocco; Farina, Piero; Romagnoli, Enrico; Cangemi, Stefano; Bianchini, Francesco; Nesta, Marialisa; Bruno, Piergiorgio; D'Amario, Domenico; Leone, Antonio Maria; Trani, Carlo (Frontiers in Cardiovascular Medicine, 2022)
Actually transcatheter aortic valve implantation within failed surgically bioprosthetic valves (VIV-TAVI) is an established procedure in patients at high risk for repeat surgical aortic valve intervention. Although less invasive than surgical reintervention, VIV-TAVI procedure offers potential challenges, such as higher rates of prosthesis-patient mismatch and coronary obstruction. Thus, optimal procedural planning plays an important role to minimize the risk of procedure complications. In this review, we describe the key points of a VIV-TAVI procedure to optimize outcomes and reduce the risk of procedure complications.